2022
DOI: 10.3390/w14203285
|View full text |Cite
|
Sign up to set email alerts
|

Internal Erosion Experiments on Sandy Gravel Alluvium in an Embankment Dam Foundation Emphasizing Horizontal Seepage and High Surcharge Pressure

Abstract: For an internally unstable soil, fine particles can move in the pore channels between coarse particles along with seepage flow; this process is termed internal erosion. To evaluate the internal stability and internal erosion behavior of sandy gravel alluvium beneath the suspended cutoff wall in an embankment dam foundation, a series of horizontal seepage tests were carried out on the four representative gradations of the alluvium layer using a large-scale high-pressure erosion apparatus. The evolutionary trend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 32 publications
0
0
0
Order By: Relevance
“…Furthermore, the soil usually exhibits strong anisotropy, with the combination of the gravity effect, the direction of the seepage flow can affect the soil's internal stability and erosion phenomena [36]. Moreover, numerous studies have demonstrated that both the stress state and stress magnitude can have a significant effect on internal stability, as well as the erosion-induced hydraulic and mechanical responses [37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the soil usually exhibits strong anisotropy, with the combination of the gravity effect, the direction of the seepage flow can affect the soil's internal stability and erosion phenomena [36]. Moreover, numerous studies have demonstrated that both the stress state and stress magnitude can have a significant effect on internal stability, as well as the erosion-induced hydraulic and mechanical responses [37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%